2017
DOI: 10.1007/s00204-017-2002-1
|View full text |Cite
|
Sign up to set email alerts
|

Utility of spherical human liver microtissues for prediction of clinical drug-induced liver injury

Abstract: Drug-induced liver injury (DILI) continues to be a major source of clinical attrition, precautionary warnings, and post-market withdrawal of drugs. Accordingly, there is a need for more predictive tools to assess hepatotoxicity risk in drug discovery. Three-dimensional (3D) spheroid hepatic cultures have emerged as promising tools to assess mechanisms of hepatotoxicity, as they demonstrate enhanced liver phenotype, metabolic activity, and stability in culture not attainable with conventional two-dimensional he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
253
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(259 citation statements)
references
References 52 publications
3
253
3
Order By: Relevance
“…Richert et al postulated that exposure periods longer than 72 hours in human hepatocytes do not increase the DILI‐prediction rate compared with shorter exposure times. Contrary to this Proctor et al recently reported higher predictivity of liver toxicants by 3D hLiMT (14‐day treatment) vs plated D2 primary human hepatocytes (48h‐treatment). In contrast to our cytotoxicity results, Otieno et al described that TAK875 1 is not cytotoxic in hepatocytes and HepG2 cells (data were not shown) following incubation of 100 µM for 72 hours.…”
Section: Resultsmentioning
confidence: 72%
“…Richert et al postulated that exposure periods longer than 72 hours in human hepatocytes do not increase the DILI‐prediction rate compared with shorter exposure times. Contrary to this Proctor et al recently reported higher predictivity of liver toxicants by 3D hLiMT (14‐day treatment) vs plated D2 primary human hepatocytes (48h‐treatment). In contrast to our cytotoxicity results, Otieno et al described that TAK875 1 is not cytotoxic in hepatocytes and HepG2 cells (data were not shown) following incubation of 100 µM for 72 hours.…”
Section: Resultsmentioning
confidence: 72%
“…Two systematic benchmarking studies for hepatotoxicity tests have been published in PHH spheroids to date. Proctor et al used a commercial proprietary model to test the toxicity of 110 drugs (69 DILI‐positive and 41 DILI‐negative) during 14 days of repeated exposures using the InSphero model and reported overall sensitivity and specificity of 59% and 80%, respectively. In contrast, we used chemically defined media and ULA 3D PHH spheroids to expose a panel of 123 drugs (70 DILI‐positive and 53 DILI‐negative), correctly predicting the hepatotoxicity of 48 out of 70 compounds (sensitivity = 69%) without a single false‐positive result (specificity = 100%; Figure A) .…”
Section: Applications Of Advanced Primary Human Hepatocyte Culture Momentioning
confidence: 99%
“…Therefore, the risk of human DILI has been massively underestimated by the in vitro system. Similar problems exist for the category 1 compounds dantrolene, methotrexate, stavudine and trovafloxacin (Proctor et al 2017;Table S-3, S3h LiMT data). It is interesting to note that cytotoxicity allows a good prediction of human blood concentrations associated with an increased risk of DILI for some compounds, while it leads to a massive underestimation of other severe DILI compounds.…”
mentioning
confidence: 58%
“…However, a comprehensive study including a sufficiently large number of compounds for validation of these endpoints is not yet available. The merit of the present study (Proctor et al 2017) is that it delivers a comprehensive cytotoxicity database, which clearly demonstrates that cytotoxicity alone is not sufficient to predict human DILI. In conclusion, the hunt for an accurate in vitro system quantitatively predicting human hepatotoxicity has only just begun.…”
mentioning
confidence: 95%